New directions for teacher education: investigating school/university partnership in an increasingly school-based context. Issue 1 (1st January 2019) - Jackson, Alison; Burch, James
Abstract: As school-led teacher education becomes more prevalent in England and elsewhere, new challenges arise for university and school-based teacher educators (SBTEs). Against this policy backdrop we discuss the challenges faced by universities and schools. We draw on findings from our small-scale case study which looked at the practice of a group of SBTEs working in a Third Space with a boundary broker from the university sector. From these findings, we suggest a form of teacher education that synthesises school and university expertise in ways which have the potential to develop new directions for partnership from both sides of a supposed boundary. We discovered that Third-Space activity has the potential to bring about a shift in SBTEs' practices, both with student-teachers and in their everyday teaching. There was some evidence that there could be benefits to schools and universities. In particular, it seemed that the skilful use of boundary brokering, aimed at the fostering of the second-order teaching skills of teaching others to teach, was significant. We propose a series of ideas for how boundary brokering within Third-Space activity has the potential to suggest new directions for the role of both school-based and university teacher educators.